2016
DOI: 10.3346/jkms.2016.31.5.729
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Childbearing Decisions on Family Size of Korean Women with Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) predominantly affects women in their reproductive years and has a significant impact on childbearing. We investigated the influence of personal decision on family size among Korean women with SLE and factors that affect the decisions. A case-control study comparing childbearing history and decisions of 112 SLE patients and 135 controls was performed. Women with SLE participating in the Network for Lupus Clinical Research in South Korea and matching controls between ages of 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Only a Saudi Arabian study reported 15% of 400 women without SLE attending primary healthcare centres, thought fertility in men and women with SLE was affected [ 27 ]. The frequency of childlessness attributed to SLE in our population was consistent with a recently published Korean study demonstrating 31% of women with SLE decided not to have children due to health-related reasons [ 2 ]. This case–control study, however, reports the avoidance of pregnancy (55% in women with SLE compared with 41% in controls) was higher compared with our population.…”
Section: Discussionsupporting
confidence: 91%
“…Only a Saudi Arabian study reported 15% of 400 women without SLE attending primary healthcare centres, thought fertility in men and women with SLE was affected [ 27 ]. The frequency of childlessness attributed to SLE in our population was consistent with a recently published Korean study demonstrating 31% of women with SLE decided not to have children due to health-related reasons [ 2 ]. This case–control study, however, reports the avoidance of pregnancy (55% in women with SLE compared with 41% in controls) was higher compared with our population.…”
Section: Discussionsupporting
confidence: 91%
“…Maternal complications such as lupus are, hypertension, nephritis, pre-eclampsia, and eclampsia and fetal complications such as fetal loss, stillbirths, preterm birth, and intrauterine growth retardation were more frequent during pregnancy in women with SLE compared with healthy women [13][14][15]. The disease also had a signi cant psychosocial impact on family life in that many SLE women make choices to limit family size due to concerns about the health of a child and their care [16][17][18]. Thus, women of childbearing age with SLE are among the most vulnerable population needing special attention, since a high disease burden is imposed upon this particular population group.…”
Section: Introductionmentioning
confidence: 99%
“…One major reason underlying this is health-related concerns. 1,50 Although the incidence of APOs was higher in our cohort than in the general population, the risk of APOs did not differ based on the presence of prior severe organ manifestation.…”
Section: Discussionmentioning
confidence: 51%